EFEKTIVITAS PROGRAM GAME FLASH PENJUMLAHAN DALAM MENINGKATKAN KEMAMPUAN OPERASI PENJUMLAHAN BAGI ANAK BERKESULITAN BELAJAR (Single Subject Research pada Kelas III di SD N 15 Ulu Gadut, Padang) - Ragil Dewi Ratih Sulistiani (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract : This research was conducted due to the problem found in the field showing that a student named RA had difficulties to do row-down calculation with saving technique. Dealing with this problem, this research was intended to reveal the effectiveness of game flash penjumlahan program to improve calculating ability of the children with learning disabilities in the third grade of SDN 15 Ulu Gadut Padang.This was an experimental research which applied Single Subject Reseacrh and A-B-A design. The data gathered were analyzed by using visual analysis of graphic. The subject of the research was the children with learning disabilities. The variables were measured by using percentage technique. The results of the research showed that the children with learning disabilities score in the baseline (A1) condition which conducted in seven meeting was 0%, in intervention (B) condition that consisted of ten meetings was 90%, and in the baseline (A2) condition that consisted of six meetings was 90%. The result of within-condition analysis and inter-condition analysis indicated that the stability tendency and the direction tendency improved. In addition, the percentage of the data overlaped was low. Based on these results, it was concluded that the use of game flash penjumlahan program was effective to improve calculating ability of the children with learning disabilities. Therefore, it was suggested to the teacher to apply game flash penjumlahan program to teach calculation topics. Keywords  :  game flash penjumlahan program, calculation, children with learning disabilities